PENGARUH KECERDASAN SPIRITUAL IBU TERHADAP KARAKTER ANAK USIA SEKOLAH DASAR DI PERDESAAN - Puspitasari, Rety; Hastuti, Dwi; Herawati, Tin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
This study aimed to analyze the effect of mother’s spiritual quotient on child’s character among school-aged children in Ciasihan and Ciasmara village that represents villages of rural area in Bogor. The population of this study was families in rural areas who have school-age children at 4th and 5th grade in study site. The design of this study was cross sectional and involved 125 families with their children who selected by proportional random sampling. The data obtained through interviews by using structured questionnaire. The results showed that the mother’s spiritual quotient and child’s character were in medium category, while the mother’s spiritual quotient on boys’ respondent were better than girls. Meanwhile, girls’ character was better than boys. The correlation test results showed a positive and significant relationship between gender, mother’s spiritual quotient, and child’s character. Regression analysis showed that the mother’s spiritual quotient was positive and significantly influenced on child’s character.